2014
DOI: 10.1371/journal.pone.0104294
|View full text |Cite
|
Sign up to set email alerts
|

The Short-Term Effects of Exercise on Intraocular Pressure, Choroidal Thickness and Axial Length

Abstract: PurposeTo explore ocular changes in healthy people after exercise.MethodsTwenty five volunteers underwent exercise for 15 minutes on a treadmill. Measurements of choroidal thickness, intraocular pressure (IOP), ocular biometry, and blood pressure were taken before and after exercise. Enhanced Depth Imaging optical coherence tomography (EDI-OCT) was used to measure choroidal thickness at the fovea. Intraocular pressure (IOP) was measured by Goldmann applanation tonometry. Ocular biometric measures were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 32 publications
5
35
0
2
Order By: Relevance
“…There were no significant changes in the mean CCT before and after the exercise which is consistent with recent reports [2, 13]. Our results added the new information that there were no significant changes in the mean total choroidal area, the mean luminal and stromal areas after the dynamic exercise.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…There were no significant changes in the mean CCT before and after the exercise which is consistent with recent reports [2, 13]. Our results added the new information that there were no significant changes in the mean total choroidal area, the mean luminal and stromal areas after the dynamic exercise.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have reported that the IOPs were decreased after exercise [15, 7, 8]. Hong et al reported that IOPs were significantly decreased after exercise with no correlation with the choroidal thickness [2], which is consistent with our results. The changes in the IOP were not correlated with those of the choroidal structural parameters, suggesting that IOP may be less likely related to the choroidal structural changes after the exercise.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is unlikely that the effect of that diurnal variation seriously affected the conclusions of the present study because the maximum likely diurnal variation is only about 10% of the choroidal thickness (Tan et al 2012). However, the maximum likely variations of the choroidal thickness due to these factors have been reported to be <10% of the choroidal thickness (Kim et al 2013a;Hong et al 2014;Altinkaynak et al 2015). IOP = intraocular pressure.…”
Section: Discussionmentioning
confidence: 77%
“…The IOP reduction after 15 min of treadmill running at a speed of 6.5–8 km/h was 3.82 mmHg, with an additional decrease of 1.14 mmHg after 30 min (Hong et al. ). Kozobolis et al.…”
Section: Physical Exercise and Iop Controlmentioning
confidence: 99%